Properties of three-layer melamine urea formaldehyde particleboard from bamboo / Jamaludin Kasim … [et al.] - Kasim, Jamaludin; Ahmad, Abdul Jalil; Yamani, Shaikh Abdul Karim; Shafie, Amran; Wan Abdul Rahman, Wan Mohd Nazri; Othman, Ahmad Fauzi (2004)
In the study of high moisture resistant particleboard from bamboo (Gigantochloa scortechinii), three-layer melamine urea-formaldehyde particleboard was produced. Increasing core particle size does not greatly affect the mechanical properties but improved the dimensional stability of the boards. Wax addition increased the board stability towards water exposure but decreased the mechanical properties of the boards. All boards surpassed the minimum requirement of the BS for the mechanical and physical properties. Particles from three-year-old Gigantochloa scortechinii was suitable for the making of three Layer melamine urea-formaldehyde particleboard.